Artificial photosynthesis – solar fuels: current status and future prospects. Issue 6 (November 2010) - Cogdell, Richard J; Brotosudarmo, Tatas HP; Gardiner, Alastair T; Sanchez, Pedro M; Cronin, Leroy
This review considers the case for using artificial photosynthesis to make solar fuels. The conceptual framework on which this idea is based is described. Photosynthesis is broken down into four partial reactions. Each one is described and progress in mimicking each of these is discussed. Finally, the current major barriers to achieving working systems based on artificial photosynthesis capable of making solar fuels are highlighted